PROFIL SUHU DAN TEKANAN DARAH PENERIMA VAKSIN BOOSTER COVID-19 DI SENTRA VAKSIN UNTAR - Chrismerry Song; Octavia Dwi Wahyuni; Twidy Tarcisia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
The SARS-CoV-2 virus has experienced thousands of mutations and has led to the emergence of new, relatively more dangerous variants. Analysis results of several patients who were hospitalized in the period January - February 2022 showed that most of the patients who died had not been fully vaccinated. Results of the study showed a decrease in antibodies 6 months after the complete primary dose of COVID-19 vaccination, so booster dose was needed to increase individual protection. The implementation of education at Universitas Tarumanagara (UNTAR), especially medical faculty, requires face-to-face hands-on learning activities so that all components involved in these activities need to get booster vaccinations for protection. UNTAR in collaboration with health institution held community service activities in the form of giving booster vaccinations to support government programs, as well as launching academic activities. Blood pressure (< 180/110 mmHg) and temperature (<37,5oC) screening are important requirements that must be considered before receiving a booster vaccine. Measurement of blood pressure and body temperature using a sphygmomanometer and digital thermometer which is calibrated before the day of implementation. The screening is carried out to prevent the occurrence of follow-up events after immunization, worsening of the recipient's health condition, and reduction of vaccine effectiveness. A total of 666 participants attended and all of them had normal temperatures with a range between 36oC to 37.1oC. A total of 148 (22.22%) participants had normal blood pressure (blood pressure <120/80 mmHg), 250 (37.54%) participants were classified as pre-hypertension (blood pressure 120/80 and <140/90 mmHg), and 268 (40.2%) participants had hypertension. The high prevalence of hypertension is hoped can be reduced by performing â€œPATUHâ€œ and â€œCERDIKâ€ behavior. Education was carried out by the medical team of UNTAR when the blood pressure examination was found to be â‰¥ 120/80 mmHg. ABSTRAK: Virus SARS-CoV-2 hingga saat ini mengalami ribuan mutasi dan menyebabkan munculnya varian baru yang relatif lebih berbahaya. Sejumlah pasien rawat inap RS pada periode Januari - Februari 2022 menunjukkan sebagian besar pasien yang meninggal belum divaksinasi lengkap. Hasil studi menunjukkan penurunan antibodi pada 6 bulan pasca vaksinasi COVID-19 dosis primer lengkap, sehingga dibutuhkan pemberian dosis lanjutan (booster) untuk meningkatkan proteksi individu. Penyelenggaraan pendidikan di Universitas Tarumanagara (UNTAR) terutama Fakultas Kedokteran memerlukan kegiatan praktik hands-on learning secara tatap muka sehingga seluruh komponen yang terlibat perlu mendapatkan vaksinasi booster untuk perlindungan. UNTAR bekerja sama dengan instansi kesehatan menyelenggarakan kegiatan PKM berupa pemberian vaksin booster sebagai upaya mendukung program pemerintah, juga melancarkan kegiatan akademik. Penapisan berupa pemeriksaan tekanan darah (< 180/110 mmHg) dan suhu tubuh (<37,5oC) merupakan syarat penting yang harus diperhatikan sebelum menerima vaksin booster. Pengukuran tekanan darah dan suhu tubuh menggunakan tensimeter dan termometer digital yang diterima sebelum hari pelaksanaan. Penapisan dilakukan untuk mencegah terjadinya kejadian ikutan pasca imunisasi, perburukan kondisi kesehatan penerima serta pengurangan efektivitas vaksin.Â Total sebanyak 666 peserta yang hadir dan semuanya memiliki suhu normal dengan rentang suhu antara 36oC hingga 37,1oC. Sebanyak 148 (22,22%) peserta memiliki tekanan darah normal (tekanan darah <120/80 mmHg), 250 (37,54%) peserta tergolong pre-hipertensi (tekanan darah â‰¥120/80 dan <140/90 mmHg), dan 268 (40,2%) peserta memiliki tekanan darah tinggi/hipertensi. Tingginya angka prevalensi hipertensi diharapkan dapat diturunkan dengan melakukan perilaku â€œPATUHâ€ dan â€œCERDIKâ€. Edukasi dilaksanakan oleh tim medis UNTAR saat pemeriksaan tekanan darah didapatkan â‰¥120/80 mmHg